Nanocomposite of Zinc Oxide and Silica With Stable Luminescence - Mikrajuddin Mikrajuddin (Jurnal Matematika & Sains, 2003)
Nanocompsite of zinc oxide (ZnO) and silica (SiO2) has been produced by spray drying the mixture of ZnO and SiO2 colloids. Initially, ZnO colloid was produced by hydrolizing zinc acetate in ethanol solution and then reacted with lithium hydroxide solution. Colloid of ZnO containing nanometer-scaled particles was mixed with SiO2 colloid at definite fractions, atomized using an ultrasonic nebulizer and dried in a vertical reactor using nitrogen carrier gas. The produced powder showed a time independent luminescence spectra that is important for industrial applications.